Chemical inhibition of the contaminant Lactobacillus fermentum from distilleries producing fuel bioethanol - Oliva Neto, Pedro de [UNESP]; Lima, Fabíola Aliaga De [UNESP]; Silva, Ketrin Cristina Da [UNESP]; Silva, Douglas Fernandes Da [UNESP]; Carvalho, Ana Flavia Azevedo; Santos, Catarina dos [UNESP] (Instituto de Tecnologia do Paraná - Tecpar, 2014)
The purpose of this study was to determine the Minimum Inhibitory Concentration (MIC) of pure or mixed chemicals for Saccharomyces cerevisiae and Lactobacillus fermentum in the samples isolated from distilleries with serious bacterial contamination problems. The biocides, which showed the best results were: 3,4,4' trichlorocarbanilide (TCC), tested at pH 4.0 (MIC = 3.12 mg/l), TCC with benzethonium chloride (CBe) at pH 6.0 (MIC = 3.12 mg/l) and TCC mixed with benzalkonium chloride (CBa) at pH 6.0 (MIC = 1.53 mg /l). If CBa was used in sugar cane milling in 1:1 ratio with TCC, a 8 times reduction of CBa was possible. This formulation also should be tested in fermentation steps since it was more difficult for the bacterium to develop resistance to biocide. There was no inhibition of S. cerevisiae and there were only antibiotics as an option to bacterial control of fuel ethanol fermentation by S. cerevisiae.
Keywords: Ethanol; lactic acid bacteria; Saccharomyces cerevisiae; Lactobacillus fermentum